A case of misconstrue proptosis. (23rd April 2013) - Chiam, Patrick J T; Ho, Vivian W-M; Hubbard, Alan D; Weerasinghe, Suboda
Abstract : This case illustrates an overlooked metastatic lung carcinoma to the orbit. The rapid onset of symptoms and oedema mimicked a cellulitis. The patient was initially treated with a broad-spectrum topical and intravenous antibiotic therapy. The white blood cell count (WBC) and C reactive protein (CRP) were normal. Compressive optic neuropathy and serous retinal detachment ensued. The initial chest x-ray revealed lung shadows; however, this was not reviewed. Eventually, CT of the chest was organised and showed a lung mass. The management of such a case remains a challenge for the uninitiated, and high index of suspicion is required to ensure early appropriate management. Despite complete resolution of the swelling with sequential chemotherapy (cisplatin and etoposide) and radiotherapy, the visual prognosis remained grim.